Assessment of the sensitivity of thoracic injury criteria to subject-specific characteristics using human body models - Piqueras, Ana; Iraeus, Johan; Pipkorn, Bengt; López-Valdés, Francisco J. (Frontiers in Bioengineering and Biotechnology, 2023)
The 3D measurement of the chest deformation has been proposed as the best predictor of thoracic injury risk in frontal impact. The use of detailed Finite Element Human Body Models (FE-HBM) can reinforce the information obtained from physical crash tests with Anthropometric Test Devices (ATD) since FE-HBM can be exposed to omnidirectional impacts and allows the modification of the geometry to represent specific groups of the population. This study aims to assess the sensitivity of two thoracic injury risk criteria (PC-score and Cmax) to several personification techniques of FE-HBM. Three 30º nearside oblique sled tests were reproduced using the SAFER HBM v8 and three personification techniques were applied to this model to evaluate the influence on the risk of thoracic injuries. First, the overall mass of the model was adjusted to represent the weight of the subjects. Second, the model anthropometry and mass were modified to represent the characteristics of the PMHS. Finally, the spine alignment of the model was adapted to the PMHS posture at t=0 ms, to conform to the angles between spinal landmarks measured in the PMHS. Two main predictors based on the chest deformation were used to calculate the prediction of sustaining three or more fractured ribs (AIS3+) of the SAFER HBM v8 and the influence of the personification techniques: The maximum posterior resultant displacement of any studied point of the chest (Cmax) and the computed sum of the upper and lower rib points (PC score). Despite of have led to statistically significant differences on the probability of AIS3+ calculations, mass scaled and morphed version provided, in general, lower values of injury risk than the baseline model and the postured version being the latter which exhibited the better approximation to the PMHS tests in terms of probability of injury. Additionally, this study found that PC score based prediction showed higher values of p(AIS3+) than the prediction based on Cmax for the loading conditions and personification techniques analyzed within this study.